Advances in Dynamic Games and Applications 2000
DOI: 10.1007/978-1-4612-1336-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of a Dynamic Duopoly Game with Bounded Rationality

Abstract: A dynamic Cournot duopoly game, characterized by finns with bounded rationality, is represented by a discrete-time dynamical system of the plane. Conditions ensuring the local stability ofa Nash equilibrium, under a local (or myopic) adjustment process, are given, and the influence ofmarginal costs and speeds of adjustment of the two finns on stability is studied. The stability loss ofthe Nash equilibrium, as some parameter ofthe model is varied, gives rise to more complex (periodic or chaotic) attractors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
158
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(161 citation statements)
references
References 15 publications
1
158
1
Order By: Relevance
“…To give a specific form for dynamics (10), in our model we also assume linear inverse demand function [5,9,10,13,14,18,23,24,26,[32][33][34]:…”
Section: Two Different Delay Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…To give a specific form for dynamics (10), in our model we also assume linear inverse demand function [5,9,10,13,14,18,23,24,26,[32][33][34]:…”
Section: Two Different Delay Structuresmentioning
confidence: 99%
“…Bischi and Naimzada [9] first gave the general formula of bounded rationality in a duopoly game, where each firm uses the local knowledge of its marginal profit to adjust strategy in a new period: increasing its output if it perceives a positive marginal profit and decreasing its production if the perceived marginal profit is negative. A great deal of research work has been done for the dynamical Cournot game played by homogeneous players with such a kind of rationality (e.g., [9][10][11][12]). …”
Section: Introductionmentioning
confidence: 99%
“…Puu [10,11] discussed the dynamical properties of the Cournot oligarchic model and 2 Discrete Dynamics in Nature and Society indicated that it will not converge to Nash equilibrium unless it is a complex trajectory. And the dynamical properties of the bounded rational duopoly model are also studied in [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the dynamic study of economics, a couple of economic models represented by difference equations are investigated, such as the classical cobweb model describing the variation of the supply and demand, the Cournot models of oligopoly, and so on [2], [1], [6], [11]. It is well known that Bertrand duopoly competition game is one of the basic oligopoly games with two players.…”
Section: Introductionmentioning
confidence: 99%